Cytosolic [Ca2+] regulation of InsP3-evoked puffs. - Yamasaki-Mann, M; Demuro, A; Parker, I (2013)
InsP3-mediated puffs are fundamental building blocks of cellular Ca2+ signalling, and arise through the concerted opening of clustered InsP3Rs (InsP3 receptors) co-ordinated via Ca2+-induced Ca2+ release. Although the Ca2+ dependency of InsP3Rs has been extensively studied at the single channel level, little is known as to how changes in basal cytosolic [Ca2+] would alter the dynamics of InsP3-evoked Ca2+ signals in intact cells. To explore this question, we expressed Ca2+-permeable channels (nicotinic acetylcholine receptors) in the plasma membrane of voltage-clamped Xenopus oocytes to regulate cytosolic [Ca2+] by changing the electrochemical gradient for extracellular Ca2+ entry, and imaged Ca2+ liberation evoked by photolysis of caged InsP3. Elevation of basal cytosolic [Ca2+] strongly increased the amplitude and shortened the latency of global Ca2+ waves. In oocytes loaded with EGTA to localize Ca2+ signals, the number of sites at which puffs were observed and the frequency and latency of puffs were strongly dependent on cytosolic [Ca2+], whereas puff amplitudes were only weakly affected. The results of the present study indicate that basal cytosolic [Ca2+] strongly affects the triggering of puffs, but has less of an effect on puffs once they have been initiated.